2023
DOI: 10.1007/s00227-023-04220-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth and morphology of Critically Endangered green sawfish Pristis zijsron in globally important nursery habitats

Abstract: Understanding growth rates and other basic life-history information of imperilled species is essential to assessing the extent of threats to a population, but often difficult due to limited access to study subjects. Here we used mark-recapture data to estimate growth rates of juvenile Critically Endangered green sawfish (Pristis zijsron) in a globally important nursery in the eastern Indian Ocean (Western Australia). Our results suggest that growth of juvenile sawfish in this part of the central Western Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…A total of 90 half sibling dyads were identified amongst all sampled individuals (Figure 2), involving 67 genotyped P. zijsron Catch data also indicated that one paternal half sibling dyad was pupped at roughly the same time; 2011 #06 was sampled six months prior to its half siblings 2011 #28 (Figure 2b), with the difference in TL (209 mm) consistent with local growth rates (Lear et al, 2023). It was estimated that the remaining paternal half siblings were pupped at least 5 months and up to 12 years apart, and were conceived by up to five dams for any single group.…”
Section: Kinshipmentioning
confidence: 84%
See 2 more Smart Citations
“…A total of 90 half sibling dyads were identified amongst all sampled individuals (Figure 2), involving 67 genotyped P. zijsron Catch data also indicated that one paternal half sibling dyad was pupped at roughly the same time; 2011 #06 was sampled six months prior to its half siblings 2011 #28 (Figure 2b), with the difference in TL (209 mm) consistent with local growth rates (Lear et al, 2023). It was estimated that the remaining paternal half siblings were pupped at least 5 months and up to 12 years apart, and were conceived by up to five dams for any single group.…”
Section: Kinshipmentioning
confidence: 84%
“…Captured individuals were then released at the site of capture. All sawfish sampled were either young of the year (YOY or 0+) or juveniles older than one year of age (referred to as 'juveniles'), with age classes assigned based on regional growth rate information reported for P. zijsron by Lear et al (2023). Samples were collected from a total of 114 immature P. zijsron: 40 between 2011 and 2014 (21 YOY; 19 juveniles), and 74 between 2020-2022 (56 YOY; 18 juveniles) (Table 1).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high occurrence of green sawfish within the study region and presence of all size classes highlights the value of the area for this threatened species. It is established that green sawfish are born annually in and around the Ashburton River estuary (Onslow region), which they utilize as a nursery for extended periods (Morgan et al, 2015;Lear et al, 2023) and subsequently expand their range into other nearby creeks (Morgan et al, 2017). However, small numbers of neonates/juveniles were also observed along coastal areas of the Pilbara and the Exmouth Gulf, and juveniles have also been reported to the north and south of the study area (Morgan et al, 2011;Whitty et al, 2014; Department of Primary Industries and Regional Development, 2020).…”
Section: Pristidaementioning
confidence: 99%
“…And it is the largest sawfish species of family Pristidae, reaching an impressive length of up to 24 feet. In Australia, the distribution of green sawfish is from the east coast of the central Pacific Ocean, around the northern continent, to Shark Bay in the south-west to the eastern Indian Ocean, but the population in north-eastern Australia has now declined dramatically, and may even be extinct along much of the east coast of Australia [12][13][14]. On the contrary, the species is still regularly found in western Australia.…”
Section: Introductionmentioning
confidence: 99%